2019
DOI: 10.6007/ijarafms/v9-i3/6353
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Good Corporate Governance on Investment Decisions and Profitability and Its Impact on Corporate Value

Abstract: This study aims to analyze the effect of Good Corporate Governance on Investment Decisions and Profitability and Its Impact on Corporate Value. The sampling technique used is purposive sampling. The study was conducted on companies that are included in the LQ45 Index with the 2015-2017 study periods. The estimation of the research model used is multiple regression analysis. The purposes of this study are to find out whether Good Corporate Governance has an effect on Investment Decisions and Profitability and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
0
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
2
0
0
4
Order By: Relevance
“…Although these correlations are not strong but they are significant. In support of our results, the studies of Jayaraman (2012) and Wahyudi and Chairunesia (2019) provided strong evidence that the corporate governance, perception of insider trading laws and investment decision are associated with each other. Other studies e.g.…”
Section: Correlation Testsupporting
confidence: 86%
See 1 more Smart Citation
“…Although these correlations are not strong but they are significant. In support of our results, the studies of Jayaraman (2012) and Wahyudi and Chairunesia (2019) provided strong evidence that the corporate governance, perception of insider trading laws and investment decision are associated with each other. Other studies e.g.…”
Section: Correlation Testsupporting
confidence: 86%
“…The study of Miloud (2017) concluded that a good corporate governance practices not only link with investment but eventually played its role in business growth (Fazal, Bhatti, & Ahmad, 2019). Similar results consistent with this study are found in the study of Wahyudi and Chairunesia (2019) which aimed to analyze the impact of good corporate governance practices on investment and profitability. In Vietnam, the corporate structure and managerial decisions taken in 480 Small and Medium Size Industries were investigated by Chi, Van Can, and Duc (2019), the results demonstrated that companies where manager hold shares has more opportunities of investment, whereas the revenue growth and financial leverage have also a positive impact on the investment decisions.…”
Section: Regression Analysissupporting
confidence: 84%
“…Kepemilikan manajerial tidak berpengaruh terhadap keputusan investasi, kepemilikan institusional berpengaruh negatif terhadap keputusan investasi, kepemilikan manajerial tidak berpengaruh terhadap profitabilitas, kepemilikan institusional tidak berpengaruh terhadap profitabilitas, dan kepemilikan manajerial berpengaruh positif terhadap nilai perusahaan. Keputusan investasi berpengaruh positif terhadap nilai perusahaan, sedangkan profitabilitas berpengaruh signifikan terhadap nilai perusahaan (Wahyudi & Chairunesia, 2019). Praktik tata kelola perusahaan cenderung memiliki dampak yang signifikan terhadap laba per saham dan mengungkapkan dikotomi praktik tata kelola perusahaan berdasarkan arah hubungannya dengan nilai pemegang saham dan mengistilahkannya sebagai pendorong nilai dan penghambat nilai.…”
Section: Pendahuluanunclassified
“…Kehadiran dewan, independensi dewan, non-dualitas peran CEO-Ketua terhadap nilai perusahaan yang terdaftar adalah penting. Praktik pro-entrenchment cenderung menurunkan laba per saham di perusahaan-perusahaan yang terdaftar baik karena rasa puas diri atau kepentingan pribadi (Wahyudi & Chairunesia, 2019).…”
Section: Pendahuluanunclassified
“…uai dengan pen. elitian d. ilakukan o. leh Farida et al (2019), Suryato & Meisa (2016), dan Wahyudi & Chairunesia (2019) menyatakan kepemilikan manajerial berpengaruh positif pada nilai perusahaan.…”
Section: Tabel 5 Hasil Uji Autokorelasiunclassified